Artikel Review: Produksi Gas Hidrogen dari Reaksi Elektrolisis Sebagai Bahan Bakar Non-Fosil - Nurlatifah, Ismi; Arlianti, Lily (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
In carrying out various activities today, it cannot be separated from the fuel. As we all know, fuels that are still commonly used today are fossil fuels whose energy resources are running low. Not only that, fossil fuels have also been shown to produce air pollution. Unhealthy air conditions can certainly reduce human life expectancy. In order to make the clean environment and not polluted by the air pollution, there must be environmentally friendly fuels. The answer for this kind of fuels is hydrogen which comes from nonfossil. One way to obtain hydrogen is an electrolysis reaction. Water can produce hydrogen through electrolysis. Just a few liters of water, it can produce ten to twenty thousand liters of hydrogen gas per hour. The use of Hydrogen as a non-fossil fuel has been proven to be environmentally friendly and free of carbon monoxide. Healthy air and a clean environment are certainly our responsibility. It's time to switch by using hydrogen fuel.